The Book of Tiny Prayer : Daily Meditations from the Plague Year - Bucey, Micah (Book collections on Project MUSE., 2022)
"When New York City went into lockdown in March 2020, spiritual leader Micah Bucey found the world and himself in desperate need of prayer. While social distancing created disconnect, Bucey began a daily practice of writing a "Tiny Prayer" each morning and posting it on social media, each offering a reflection on what was going on in his own heart and in the wider world. Soon, a solitary practice became a communal one, with others engaging and sharing the prayers that touched them most, suggesting issues and topics for future prayers, and creating connection across a digital divide. Over the course of a year filled with fear and faith, protest and possibility, Bucey composed prayers for frontline workers and activists, those lost to illness and wins for democracy, for civic leaders, celebrities, and everyday emotions. While overwhelm threatened to engulf us all, these short meditations invited a combination of attention and intention in bite-sized form that aided the reader in focusing on one issue at a time, from the rise of infections, hospitalizations, and deaths, to police violence, social justice uprisings, immigrant detentions, catastrophic climate events, mass shootings, and violent right-wing insurrections. Now, all 366 "Tiny Prayers" are collected here, together forming a chronicle of a specific moment in time and modeling a form for everyone to compose their own tiny prayers to engage the everyday around them. The Book of Tiny Prayer recalls a very particular year, but its spirit is universal, inviting all to quiet themselves, name the pain and the joy around them, and recommit to the change required for collective liberation, during the worst times and far beyond"--